2007
DOI: 10.1158/1078-0432.ccr-06-1657
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Molecular Imaging Sheds Light on the Synergy between 5-Fluorouracil and TRAIL/Apo2L for Cancer Therapy

Abstract: Purpose: In a previous report, a recombinant luciferase reporter, activated during apoptosis via caspase-3 cleavage, was developed for imaging of apoptosis using bioluminescence. The ability to noninvasively image apoptosis in vivo could dramatically benefit the preclinical development of therapeutics targeting the apoptotic pathway. In this study, we examined the use of 5-fluorouracil (5-FU) for sensitizing D54 tumors to tumor necrosis factor a^related apoptosis^inducing ligand (TRAIL) therapy by monitoring a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 21 publications
1
18
0
Order By: Relevance
“…Pan et al (34) found combination of TRAIL-carrying adenoviral vector with cisplatin showed an apparent synergistic cytotoxicity in cancer cells, and at the same time significantly abolished the toxicity in normal cells by reducing the dosage. Concomitant 5-FU and TRAIL therapy enhanced apoptotic activity and reduced the requirement for 5-FU that ultimately results in minimizing risks for systemic side effects (35,36). Our results confirmed the previous results.…”
Section: Discussionsupporting
confidence: 90%
“…Pan et al (34) found combination of TRAIL-carrying adenoviral vector with cisplatin showed an apparent synergistic cytotoxicity in cancer cells, and at the same time significantly abolished the toxicity in normal cells by reducing the dosage. Concomitant 5-FU and TRAIL therapy enhanced apoptotic activity and reduced the requirement for 5-FU that ultimately results in minimizing risks for systemic side effects (35,36). Our results confirmed the previous results.…”
Section: Discussionsupporting
confidence: 90%
“…In one example, two estrogen-regulatory domains were linked on both the amino-and carboxy-terminal end of luciferase with a DEVD cleavage site. 13,14 Similarly, a multimodality imaging reporter was also recently described to be composed of fluorescent, bioluminescent, and positron emission In vivo apoptosis imaging by Z-DEVD-aminoluciferin J Hickson et al tomography (PET) reporters, separated by DEVD linkers. 26 In both models, under apoptotic conditions, the reporter domains are liberated allowing for light production.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 Several recent reports have described the development of fluorescent and/or bioluminescent reporter constructs that specifically allow monitoring of caspase activation in vivo. These molecular imaging studies have mainly focused on generating cells that express a modified reporter protein, commonly a fusion protein or a split luciferase protein complementation strategy [13][14][15] that takes advantage of the specificity of caspases to cleave exclusively after aspartic acid residues and, in particular, the DEVD (aspartic acid-glutamic acid-valine-aspartic acid) tetrapeptide sequence, which is optimal for apoptotic effector caspases-3 and -7. 16,17 In these models, light production is silenced unless the cell is undergoing apoptosis, at which time activated caspase liberates the reporter.…”
mentioning
confidence: 99%
“…This reporter was then inserted in cancer cells and used as an early detector of induced apoptosis. This group has reported additional bioluminescence methods to detect apoptosis (Lee et al 2007;Rehemtulla et al 2004). Liu and colleagues (2005) have developed a luciferin substrate that was cleaved to an active form after induction of apoptosis.…”
Section: Specialized Research Applicationsmentioning
confidence: 99%